Risk factors and prevalence of enteroparasitic diseases in Shellfish Pickers from a lake area in the Northeast of Brazil - Santos, Rawanderson dos; Porto, Wagnner José Nascimento; Moraes, Anna Amélia de Paula; Wanderley, Flaviana Santos (ABCS Health Sciences, 2020)
Introduction: Intestinal parasitosis are a public health problem worldwide. There are several risk factors and a high association with some specific labor activities. Objective: The present study assessed the risk factors and prevalence of enteroparasitic diseases in shellfish pickers from one district of Maceió, Alagoas state, Brazil. Methods: Cross-sectional study of 41 female shellfish pickers including parasitological tests in fecal samples and a questionnaire with objective and subjective questions. Sand samples from their working environment were also analyzed. Results: At least one species of parasite was found in 19.51% of the fecal samples. Pathogenic species of Giardia lamblia, Trichuris trichiura, Schistosoma mansoni, Ascaris lumbricoides, Enterobius vermicularis, from the Ancylostomatidae family, and non-pathogenic species of Entamoeba coli were found. Polyparasitism was diagnosed in 37.5% of the positive samples. A total of 57.14% of sand samples contained hookworm larvae. Regarding the risk factor, low educational level was statistically associated to the presence of parasites (p<0.05). Conclusion: Greater investment in basic education is needed to increase the knowledge about preventive measures against parasitic diseases and the promotion food-handling courses in order to change existing inadequate habits in the community. Basic sanitation is also essential in preventing environmental contamination.